2013
DOI: 10.1002/etc.2274
|View full text |Cite
|
Sign up to set email alerts
|

Low temperatures enhance the toxicity of copper and cadmium toEnchytraeus crypticusthrough different mechanisms

Abstract: Knowledge about how toxicity changes with temperature is important for determining the extent of safety factors required when extrapolating from standard laboratory conditions to variable field scenarios. In the present study, the authors evaluated the toxicity of Cu and Cd to the potworm Enchytraeus crypticus at 6 temperatures in the range of 11 °C to 25 °C. For both metals, reproductive toxicity decreased approximately 2.5-fold with increasing temperature. This is contrary to what most other studies have fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 37 publications
1
30
2
Order By: Relevance
“…When the uncontaminated controls are affected by one stressor, in this Time (d) 16 and increase in length of newly hatched nematodes (C,D) as a function of time after hatching for nematodes exposed to 0, 1, 5, and 10 mg Cd/L and grown at 15 and 208C. Although internal Cd concentrations were not measured in the present study, uptake rates of Cd have been shown to increase with increasing temperature in D. magna and the potworm Enchytraeus crypticus, and also in studies on plants and algae [19,[27][28][29]. 2), whereas brood size is described with a log-logistic function (Eqn.…”
Section: Discussionmentioning
confidence: 48%
“…When the uncontaminated controls are affected by one stressor, in this Time (d) 16 and increase in length of newly hatched nematodes (C,D) as a function of time after hatching for nematodes exposed to 0, 1, 5, and 10 mg Cd/L and grown at 15 and 208C. Although internal Cd concentrations were not measured in the present study, uptake rates of Cd have been shown to increase with increasing temperature in D. magna and the potworm Enchytraeus crypticus, and also in studies on plants and algae [19,[27][28][29]. 2), whereas brood size is described with a log-logistic function (Eqn.…”
Section: Discussionmentioning
confidence: 48%
“…However, terrestrial enchytraeids (potworms) are a standard soil toxicity test organism and are sensitive to elevated Cu and other metals in moist soil. Severe declines in taxa richness have been noted by about 200 mg/kg dw Cu in soil, with low-effects thresholds occurring at less than 100 mg/kg dw Cu (Maraldo et al, 2006;Cedergreen et al, 2013). We were unable to evaluate whether enchytraeids were sensitive to Cu or Co in other stream studies, because most studies we reviewed on effects of metals in lotic systems did not report actual taxonomic data, and of those that did, oligochaetes were not identified beyond "Oligochaeta."…”
Section: Benthic Macroinvertebratesmentioning
confidence: 99%
“…Heugens et al (2003) studied the influence of temperature (10, 20, and 26 8C) on cadmium (Cd) uptake kinetics in Daphnia (0-45 h of exposure) and showed that the uptake rate constant (k u ) at 20 8C was significantly higher than at 10 8C and that the k u at 26 8C was similar to that at 20 8C. Temperature-acclimated Danio rerio (zebrafish) and Enchytraeus crypticus (a terrestrial worm) exhibited an increase in Cd accumulation with increased temperature, but no corresponding increase in toxicity (Vergauwen et al 2013;Cedergreen et al 2013). Temperature-acclimated Danio rerio (zebrafish) and Enchytraeus crypticus (a terrestrial worm) exhibited an increase in Cd accumulation with increased temperature, but no corresponding increase in toxicity (Vergauwen et al 2013;Cedergreen et al 2013).…”
Section: Introductionmentioning
confidence: 99%